Comprehensive analysis of the carboxylesterase gene reveals that NtCXE22 regulates axillary bud growth through strigolactone metabolism in tobacco - Wang, Lin; Xie, Xiaodong; Xu, Yalong; Li, Zefeng; Xu, Guoyun; Cheng, Lingtong; Yang, Jun; Li, Lei; Pu, Wenxuan; Cao, Peijian (Frontiers in Plant Science, 2022)
Carboxylesterase (CXE) is a hydrolytic enzyme with an α/β-folding domain that plays a vital role in plant growth, development, stress response, and activation of herbicide-active substances. In this study, 49 Nicotiana tabacum L. CXE genes (NtCXEs) were identified using a sequence homology search. The basic characteristics, phylogenetic evolution, gene structure, subcellular location, promoter cis-elements, and gene expression patterns of the CXE family were systematically analyzed. RNA-seq data and quantitative real-time PCR showed that the transcriptional level of CXEs was associated with various stressors and hormones; gene expression level was significantly different among the eight tissues examined and at different developmental periods. As a new hormone, strigolactone (SL) is released from the roots of plants and can control the germination of axillary buds. NtCXE7, NtCXE9, NtCXE22, and NtCXE24 were homologous to Arabidopsis SL hydrolase AtCXE15 and changes in their transcriptional levels were induced by topping and by the GR24 (synthetic analogue of strigolactone). Further examination revealed that ntcxe22-mutant plants generated by CRISPR-Cas9 technology had shorter bud outgrowth with lower SL content. Validation of NtCXE22 was also performed in NtCCD8-OE plants (fewer axillary buds) and in ntccd8 mutant plants (more axillary buds). The results suggest that NtCXE22 may act as an efficient SL hydrolase and that it affects axillary bud development, thereby providing a feasible method for manipulating endogenous SLs in crops and ornamental plants over time and space.